EFFECT TURMERIC ACID CONSUMPTION ON THE MENSTRUAL PAIN IN YOUNG WOMEN IN AL-HAMID ISLAMIC BOARDING SCHOOL JAKARTA AND NUR MEDINA ISLAMIC BOARDING SCHOOL TANGERANG - Puspa Emil Utari; Desmawati (FIKES, UPNVJ, 2019)
Painful menstruation or called dysmenorrhea is pain felt in the lower abdomen and can cause discomfort to the individual. The purpose of this study was to determine the effect of turmeric acid consumption on the level of menstrual pain in adolescent girls in Islamic boarding school (IBS) Al-Hamid, Jakarta and IBS Nur Medina, Tangerang. Method; This study is a quasi-experimental design, one group pretest and posttest with 25 participants from March to June 2019. Univariate analysis using the frequency and proportion. The bivariate analysis using paired t-test with p-value ​​= <0.05. Results showed that there are significant effect of turmeric acid consumption on menstrual pain after post-intervention with p- value = 0.000 (P <0.05). Conclusion; Teenage girls are suggested to consumptive of turmeric acid before and during menstruation.